Industrial training report: Perbadanan Perpustakaan Awam Selangor / Syahirah Athirah Saleh - Saleh, Syahirah Athirah (Faculty of Information Management, 2023)
This report describes the internship I spent at Selangor Public Library Corporation in Shah Alam. The Raja Tun Uda library is public library located in Shah Alam and worked as headquarters of Selangor Public Library Corporation. Industrial training is crucial and it helps in developing professional attitudes. The purpose of industrial training is to develop awareness of industrial approach based on the operation of organization. In addition, students can receive skills and technical knowledge outside the classes. During a period of five months industrial training at PPAS, I was assigned to variety of duties which involved with every aspect of library management. Moreover, I managed to be working on several projects and tasks, it will help the organization to fulfill the need of their users. This well worth and rewarding experience, I am able to implement what I have learnt for the past 3 years as a Bachelor Information Science (Hons.) Library Management students in Universiti Teknologi MARA Campus Rembau. It was a great experience and great opportunity to be working with Selangor Public Library Corporation and it will last a lifetime.